Fatty acid profile, carcass and quality traits of meat from Nellore young bulls on pasture supplemented with crude glycerin - Vito, E. San [UNESP]; Lage, J. F. [UNESP]; Ribeiro, A. F. [UNESP]; Silva, R. A. [UNESP]; Berchielli, Telma Teresinha [UNESP] (Elsevier B.V., 2015)
The aim of this study was to evaluate the carcass traits and meat quality of Nellore bulls (279.5 16.3 initial body weight) raised on pasture supplemented with crude glycerin at 0%, 7%, 14%, 21% or 28% (DM basis). The diets were similar in energy and protein levels, and the glycerin replaced corn in the supplement. After slaughter, the carcass characteristics were measured, and the longissimus muscle was collected to determine the meat quality. The inclusion of crude glycerin in the supplement did not change (P > 0.05) any of the carcass characteristics and meat quality assessed; however, the pH decreased linearly (P = 0.03), and margaric acid (17:0) increased (P = 0.02) in the longissimus muscle with the addition of glycerin in the diet. Our conclusion is that the inclusion of crude glycerin up to the level of 28% of dry matter in the supplement does not alter the carcass characteristics or the meat quality from animals raised on pasture. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Beef; Biodiesel co-products; Corn; Forage; Glycerol